The relevance of CT-based geometric and radiomics analysis of whole liver tumor burden to predict survival of patients with metastatic colorectal cancer - Mühlberg, Alexander; Holch, Julian; Heinemann, Volker; Huber, Thomas; Moltz, Jan; Maurus, Stefan; Jäger, Nils; Liu, Lian; Froelich, Matthias F.; Katzmann, Alexander; Gresser, Eva; Taubmann, Oliver; et al. (European radiology, 2021)
To investigate the prediction of 1-year survival (1-YS) in patients with metastatic colorectal cancer with use of a systematic comparative analysis of quantitative imaging biomarkers (QIBs) based on the geometric and radiomics analysis of whole liver tumor burden (WLTB) in comparison to predictions based on the tumor burden score (TBS), WLTB volume alone, and a clinical model.